Spot urine protein/creatinine ratio as a reliable estimate of 24-hour proteinuria in patients with immunoglobulin A nephropathy, but not membranous nephropathy - Seiji Kobayashi; Hoichi Amano; Hiroyuki Terawaki; Makoto Ogura; Yoshindo Kawaguchi; Takashi Yokoo (BMC Nephrology, 2019)
Abstract Background Proteinuria is known to be associated with both kidney function deterioration and cardiovascular diseases. While proteinuria estimation from 24-h urine samples has traditionally been considered as the standard method for assessment of the degree of urinary protein excretion, sample collection is associated with several technical problems such as inaccurate collection and the potential spread of drug-resistant pathogens. Therefore, the spot urine protein/creatinine ratio (PCR) assessment is currently recommended as an alternative. While the utility of PCR has been validated, studies on the association between spot urine PCR and 24-h proteinuria (24HP) in patients with chronic glomerular nephritis (CGN) and nephrotic syndrome (NS) are limited. This study aimed to evaluate whether an estimated result from a spot urine PCR could sufficiently approximate the daily urine protein excretion amount from a 24-h urine sample in patients with immunoglobulin A nephropathy (IgAN), minimal change disease (MCD), and membranous nephropathy– nephrotic syndrome (MN-NS). Methods The study participants included 161 patients with IgAN, MCD, or MGN-NS at the Jikei University Kashiwa Hospital and Kanagawa Prefecture Shiomidai Hospital. The correlation between spot urine PCR and a 24-h urine protein was investigated using linear regression analysis with Spearman’s correlation (r) coefficient and intraclass correlation coefficient (ICC). Results While high correlation coefficients (r = 0.86, P < 0.001) and substantial agreement (ICC: 0.806, P < 0.001) were observed in patients with IgAN, similar correlations were not observed in patients with MCD or MN-NS. In the patients with MCD, r was 0.53 (P < 0.001), which signified a slight correlation, and in the patients with MN-NS, r was 0.289 (P = 0.17), which was not statistically significant. Conclusions This study revealed that spot urine PCR is a reliable estimate of 24HP value in patients with IgAN. In contrast, there is a considerable difference between the daily urine protein excretion amount based on a 24-h urine sample and that which is calculated from spot urine PCR in patients with NS.